PENGEMBANGAN MATERI PENDIDIKAN AGAMA ISLAM BERBASIS E-MOBILE INSTRUMENTAL - Remiswal Remiswal; Arham Junaidi Firman (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
The rapid development of technology requires education practitioners to innove in developing materials that are integrated with technological developments. This type of research is a 4D R&D model with research subjects in Class X MIA.7 SMAN 10 Padang. The results of the study show, first, defining e-mobile instrumental-based PAI material shows the SMAN 10 Padang does not close itself from the development of the times. Second, the design of e-mobile instrumental-based PAI material is presented in two e-book variants, namely: Te-book and Se-book. Third, the test results for the validity feasibility of the material, language, contextual, presentation and visual aspects indicate is valid. Meanwhile, the model effectiveness test is accepted at 1% significance level. Fourth, diseminate the development of PAI material based on e-mobile instrumental conducted through focus group discussion (FGD) at SMAN 10 Padang and UIN Imam Bonjol Padang.